A profession in transition: actors, tasks and roles in AI-based accounting. Issue 3 (12th February 2021) - Leitner-Hanetseder, Susanne; Lehner, Othmar M.; Eisl, Christoph; Forstenlechner, Carina
Abstract : Purpose: This article ties in with current debates on the digital transformation of society and the consequent work changes. Using an artificial intelligence (AI)-based accounting context, the focus of this paper is on actors, roles and tasks and related skills on an individual level. The authors look at the effect of AI-based "smart" technology on the workforce in the broader accounting profession taking an intrafirm perspective, yet acknowledging that the digital transformation encompasses a much larger field in the financial sector. Design/methodology/approach: The authors conduct a Delphi study to identify the new roles and tasks in future accounting. In addition, the authors use expert workshops to clarify the related tasks and skills and determine whether either humans or AI-based technologies perform the roles or collaborate in professional accounting occupations. Findings: The results show that tasks and skills for existing professional occupations in the broader acounting context will be subject to major changes in the next 10 years due to (AI based) digital technologies, while "core" roles and tasks will continue to exist in the future, some will not be performed by humans but by AI-based technology. For other "new" roles, humans will need to make informed use of digital technologies and, to some extent, collaborate with AI-based technology. Research limitations/implications: The authors look at the effect of AI-based "smart" technology on the workforce in the broader accounting profession, taking an intrafirm perspective. Practical implications: This article ties in with current debates on the digital transformation of society and the consequent work changes. Using an AI-based accounting context, the focus of this paper is on the new and adapted roles and tasks. Originality/value: The comprehensive analysis based on the Delphi study and expert workshops provide ample innovative ground for future research on the impact of AI on organisations and society.